Strategi Komunikasi Marketing Public Relations Kopi Bajawa Flores Guna Membangun Brand Image Pada Media Sosial Instagram - Darmanto Sinambela; Edwin Rizal; Agus Rahmat (Peneliti.net, 2023)
The role of social media is very important in the current communication process. Including Instagram social media. Currently, there are more and more Instagram accounts on social media that are used to build a brand image. The use of Instagram is a way for businesses to promote goods, products, services and services. Bajawa Flores Coffee NTT is one of the coffee outlets that uses Instagram as a medium to build a brand image for their products. With the typical coffee characteristics of East Nusa Tenggara, it is unique compared to other competitors. Apart from that, Kopi Bajawa Flores also collaborates with the Tangan Pengharapan Foundation in social activities to help educate underprivileged children in NTT. This study aims to find out what are the Marketing Public Relations (MPR) communication strategies for Bajawa Coffee Flores NTT on the Instagram business media @kopibajawaflores.id in order to build a brand image for Bajawa Coffee Flores NTT. This research was conducted at Kopi Bajawa Flores, NTT, which has an office at Jalan Kedoa Raya No. 36, West Jakarta, DKI Jakarta. The results of this study indicate a marketing public relations strategy carried out by Kopi Bajawa Flores NTT on Instagram @kopibajawaflores.id to build a brand image, namely by making various advertisements and sales promotions, social enterprise activities, procurement of live music, publicity and direct marketing on Instagram Bajawa Coffee @kopibajawaflores.id. So that all marketing public relations activities carried out through the Instagram social media of Kopi Bajawa @kopibajawaflores.id are very good and need to be maintained in building the brand image of Bajawa coffee. Keywords: Strategy, Marketing Public Relations, Brand, Image, Bajawa Flores